PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI PUSAT GROSIR CILILITAN - Kasmanto Miharja (Universitas Mercu Buana, 2013)
Abstract: The research was conducted at PT. Prima Graha Citra as an organizer ofPusat Grosir Cililitan. The purpose of this study was to determine the effect of themarketing mix on purchase decisions stall/ counter in Pusat Grosir Cililitan Navel eitherpartially or jointly. The method in this study using simple linear regression analysis todetermine the effect of each independent variable on the dependent variable andMultiple Linear regression analysis to determine the effect of independent variables onthe dependent variable simultaneously.The results of a simple linear regression analysisstates that each independent variable affects the dependent variable to see t countgreater than t table and the level of influence of each with respect to the value of thecoefficient of determination with the help of SPSS. Multiple linear regression analysisalso showed that all independent variables jointly affect the dependent variable to see ifthe value of the coefficient of determination results data using SPSS.Key words: marketing mix, Purchase Decision, determinantion, coefficient.